Nationality and perception of factors impacting decisions to attend the Olympic Games before and after COVID-19 - Tiell, B. (Sport and Society, 2020)
The global pandemic caused by the spread of the COVID-19 virus in 2020 has impacted the sports industry in unprecedented ways that will remain at the forefront of how practitioners organize, market, and operate live sport events at every level. A study assessing nine factors impacting a decision to attend the 2016 Olympics in Rio de Janeiro, Brazil found that the fear of contracting the zika virus was the leading concern for citizens born in the United States (U.S.) while citizens from China ranked terrorism, riots, and street violence higher than zika. The nine factors were categorized into three clusters representing 1) environmental health concerns (e.g., zika virus and water contamination), 2) safety and security risks (e.g., terrorism, street crime, riots), and 3) personal issues (e.g., lack of time/finances, no passport, health issues, and unknown factors). A significant difference (p < .05) was found in the combined mean scores of natural citizens from the U.S. and China for each cluster. The study sparks inquiry into whether a significant difference would still exist between Chinese and U.S. citizens` perceptions of whether environmental health factors impact decisions to attend the Olympics if COVID-19 replaced the zika virus and the context applied to the 2020 Games in Tokyo which were postponed until 2021.